Effectiveness of Event-Based Augmented Reality Media in Social Studies Learning - Iqbal Pratama; Muhammad Parhan (The Innovation of Social Studies Journal, 2026)
This study aims to determine the effectiveness of using augmented reality media based on actual events in social studies learning. Sampling was conducted using a simple random sampling method. This study was conducted in 2025. The population of this study consisted of 30 seventh-grade students at SMPN 137 Jakarta in the 2025/2026 academic year in East Jakarta, Indonesia. The sampling technique used the Slovin formula to obtain a sample size of 30 seventh-grade junior high school students. This study used an experimental research method with a single group pretest-posttest design. In addition, the researcher used a paired sample t-test to test the hypothesis and a Shapiro-Wilk t-test to test normality in this study. The results of the independent sample test showed that the significance value with two tails was 0.000 < 0.05; then, as a basis for decision making in the paired sample t-test, it can be concluded that H0 is rejected, and Ha is accepted. The results show that augmented reality media based on actual events in social studies learning has a positive effect on junior high school students' learning outcomes. Augmented reality media based on actual events in social studies learning, in addition to improving learning outcomes, can also increase student motivation and engagement in learning, because it is able to provide an interactive, contextual, and immersive learning experience so that students are more interested and active in the learning process.